The impact of co-existing comorbid diseases on long-term mortality in bronchoscopic lung volume reduction - Tanrıverdi Elif; Deniz Doğan; Demet Turan; Efsun Gonca Uğur Chousein; Binnaz Zeynep Yıldırım; Barış Demirkol; Mehmet Akif Özgül; Halit Çınarka; Erdoğan Çetinkaya (Medicinski glasnik, 2019)
Aim: Emphysema is a lung disease in which alveolar capillary units are destroyed supporting tissue lost. Bronchoscopic lung volume reduction (BLVR) is a novel treatment for emphysema. Several comorbidities have been reported to coexist in patients with chronic obstructive pulmonary disease (COPD). The aim of this study was to evaluate comorbidities of patients with severe emphysema who underwent BLVR and association of these comorbidities with mortality. Methods: Between January 2011 and December 2017 the records of severe emphysema patients who underwent endobronchial valve (EBV) or lung volume reduction coil (LVRC) placement were reviewed retrospectively. Results: There were 37 patients who received EBV therapy and 29 received LVRC therapy. There were no significant differences in the demographic and clinical characteristics between two groups before the treatment. There were seven deaths (10.6%) over the period of twelve months following the BLVR treatment. All deaths occurred in patients with at least one comorbid condition. Mortality was increased in the presence of comorbidities (14.3% vs 0%, respectively; p=0.099), and it was significantly increased in the presence of multiple comorbidities (18.5% vs 0%; p=0.059). The mortality rate was higher (37.5% vs 10.5%) in the LVRC comparing to the EBV treatment group in the presence of multiple comorbid conditions, albeit not reaching statistical significance (p=0.099). Conclusion: The presence of more than one comorbidity in patients who underwent the LVRC treatment are associated with significant increase of mortality. For patients with severe emphysema who have more than one comorbidity, EBV is a better choice than LVRC.
Keywords: coil; comorbidity; COPD; endobronchial valve; emphysema